The Application of Personal Selling, Word of Mouth and Perceived Quality on Consumer Purchase Interest in Flexible Conduit Products - Sebastian, Allan William; Yuningsih, Erni; Palahudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to understanding the effect of implementing personal selling, word of mouth and perceived quality on consumer purchase interest. Customers in the target market for this study's sample are those who need flexible conduit items. The data analysis used is multiple linear regression analysis with a sample size of 70 respondents. The results in this research indicate that the simultaneous application of personal selling word of mouth and perceived quality has a positive and significant effect on consumer buying interest. Then, partially personal selling has a positive but not significant effect on consumer buying interest, while word of mouth and perceived quality have a positive and significant effect on consumer buying interest.